ASPECTS OF FISCAL POLICY OF THE STATE - M. Ibrahim (Вестник университета)
In the article explores the concept of fiscal policy, the essence of state regulation of social and economic development as a process of inclusion of the state in the economic sphere of society through of fiscal policy. Defines types of fiscal policy.